Development of a 3D cephalometric index to grade severity of dentofacial deformity in patients with juvenile idiopathic arthritis - Stratos Vassis; Mia Glerup; Ida Tambjerg; Annelise Küseler; Cory M. Resnick; Carlalberta Verna; Troels Herlin; Lillemor Berntson; Charlotte Myrup; Ellen Nordal; Marite Rygg; Kristiina Aalto; et al. (Scientific Reports)
Abstract This investigation aimed to develop a radiographic 3D cephalometric index to grade severity of dentofacial deformity in patients with juvenile idiopathic arthritis (JIA), and to perform a validation against expert evaluations. Data were collected from a population-based Nordic JIA cohort of 240 patients that received a cone-beam computed tomography (CBCT) scan approximately 17 years after onset of JIA. The cohort was randomized into two groups: A baseline group for establishing the index (n = 210) and a test group (n = 30). The standardized index generation process led to the inclusion of six radiographic outcome measures, each representing different facets of dentofacial deformities. Specific severity scores were established for three domains; dentofacial asymmetry (0–8), vertical deviation (0–8), and sagittal deviation (0–8). An overall dentofacial deformity index score was computed by aggregating the scores from the six variables, with the total score ranging from 0 to 24. The validity of the index was assessed by comparing the index score with expert evaluations. Based on the generated index, 10 patients exhibited severe deformities. Reliable agreement between data-generated index scores and expert assessments was found. A 3D radiographic dentofacial deformity index was generated and tested. This index can support an objective assessment of the severity of dentofacial deformities related to JIA in a clinical setting and future research.